Compost from coffee pulp - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Coffee pulp can be used as manure but when fresh it is very acid, slow to decompose and may spread disease. Research carried out in Brazil has shown that coffee pulp can quickly be transformed into rich organic compost by introducing a fungus,...